Tailoring the properties of Ni(111)/graphone interfaces by intercalation of Al and Na: a DFT study - Archana, Ramakrishnan; Joshi, Niharika; Raja, Thirumalaiswamy (C-Journal of Carbon, 2022)
With the incredible discovery of graphene (Gr), all of the properties studied to date suggest that it has promising applications in the development of semiconductor, spintronic, insulating, and polymer materials. However, efforts are still underway to fully understand the nature of metal–graphone(GrH) interaction in order to offer better scope for tuning the electronic and magnetic properties, which can be performed by intercalation of atoms via metal support on graphene. We chose metal atoms belonging to the s and p blocks, namely Na and Al, respectively, as the intercalating atoms. Herein, the maximum coverage of a monolayer of Na and Al was comparatively studied on a Ni(111) surface. Significant changes in the magnetic and electronic properties at the Ni(111)/graphone interface were observed upon intercalation. Of the two intercalating metal atoms, Na proved to be more effective, such that the magnetic properties of the surface Ni were only slightly decreased, and the graphone also showed better magnetic properties than in the absence of Na.